Comparison of legislation, regulations and national health strategies for palliative care in seven European countries (Results from the Europall Research Group): a descriptive study - Beek, Karen Van (BioMed Central, 2013)
BACKGROUND: According to EU policy, anyone in need of palliative care should be able to have access to it. It is therefore important to investigate which palliative care topics are subject to legislation and regulations in Europe and how these are implemented in (national) health care plans. This paper aims to deliver a structured overview of the legislation, existing regulations and the different health care policies regarding palliative care in seven European countries. METHODS: In 2008 an inventory of the organisation of palliative care was developed by the researchers of the Europall project. Included were two open questions about legislation, regulations, and health policy in palliative care. This questionnaire was completed using palliative care experts selected from Belgium, England, France, Germany, the Netherlands, Poland and Spain. Additionally, (grey) literature on palliative care health policy and regulations from the participating countries was collected to complete the inventory. Comparative analysis of country specific information was performed afterwards. RESULTS: In all countries palliative care regulations and policies existed (either in laws, royal decrees, or national policies). An explicit right to palliative care was mentioned in the Belgium, French and German law. In addition, access to palliative care was mentioned by all countries, varying from explicit regulations to policy intentions in national plans. Also, all countries had a national policy on palliative care, although sometimes mainly related to national cancer plans. Differences existed in policy regarding palliative care leave, advance directives, national funding, palliative care training, research, opioids and the role of volunteers. CONCLUSIONS: Although all included European countries have policies on palliative care, countries largely differ in the presence of legislation and regulations on palliative care as well as the included topics. European healthcare policy recommendations should support palliative care access across Europe.